1993
DOI: 10.1163/156853993x00182
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Song and Song Repertoire in the European Starling (Sturnus Vulgaris) : an Aviary Experiment

Abstract: We confronted individually-caged male European starlings, Sturnus vulgaris, with conspecifics of both sexes in order to study singing behaviour during intrasexual and intersexual encounters. Males spent more time at the nestbox, sang more songs and more song types during female presentations than during control periods (observation periods with no conspecifics). Males also sang more songs in the nestbox and flew more to the nestbox with green nest material. During male presentations, only the time spent at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 24 publications
4
74
1
1
Order By: Relevance
“…Songs produced in the presence of a female have been found to be significantly longer than those produced in isolation (Eens 1993;Kao and Brainard 2006;Sossinka and Böhner 1980). However, we did not find a significant difference in song length (exclusive of introductory notes) between UD and FD songs in the Bengalese finch (paired t-test: t 18 ϭ 0.86, P ϭ 0.3996).…”
Section: Modulation Of Other Song Featurescontrasting
confidence: 69%
See 1 more Smart Citation
“…Songs produced in the presence of a female have been found to be significantly longer than those produced in isolation (Eens 1993;Kao and Brainard 2006;Sossinka and Böhner 1980). However, we did not find a significant difference in song length (exclusive of introductory notes) between UD and FD songs in the Bengalese finch (paired t-test: t 18 ϭ 0.86, P ϭ 0.3996).…”
Section: Modulation Of Other Song Featurescontrasting
confidence: 69%
“…Context-dependent modulations of song unrelated to variability have also been noted in other songbirds (Cooper and Goller 2006;Eens 1993;Kao and Brainard 2006;Sossinka and Böhner 1980). Therefore, we examined changes to three other song features-the number of introductory notes, song length, and song tempo.…”
Section: Modulation Of Other Song Featuresmentioning
confidence: 93%
“…Instead it has been suggested that starlings use green material for mate attraction or pair bonding Fauth et al 1991;Gwinner 1997;Komdeur et al 2002). Until now, there has been no experimental support from the field for the courtship or the male quality hypotheses Fauth et al 1991;Eens et al 1993;Pinxten et al 1995;Gwinner 1997;Komdeur et al 2002).…”
Section: Lyanne Brouwer and Jan Komdeurmentioning
confidence: 99%
“…Females preferentially approach nest boxes broadcasting conspecific song compared to no song and are more likely to enter nest boxes broadcasting complex song compared to simple song (Mountjoy & Lemon, 1991). After pairing, males reduce song production, generally restricting periods of singing to immediately prior to copulation (Eens, Pinxten, & Verheyen, 1990;Eens, Pinxten, & Verheyen, 1993;Eens, Pinxten, & Verheyen, 1994) or to periods when the mate is absent (Cuthill & Hindmarsh, 1985). Additionally, males with nest boxes in spring have been found to respond to intruding males by flying to the nest site and singing, but not gathering nest material or wing waving (Eens et al, 1990;Eens et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…After pairing, males reduce song production, generally restricting periods of singing to immediately prior to copulation (Eens, Pinxten, & Verheyen, 1990;Eens, Pinxten, & Verheyen, 1993;Eens, Pinxten, & Verheyen, 1994) or to periods when the mate is absent (Cuthill & Hindmarsh, 1985). Additionally, males with nest boxes in spring have been found to respond to intruding males by flying to the nest site and singing, but not gathering nest material or wing waving (Eens et al, 1990;Eens et al, 1993). Fighting between two males in a nest hole may be accompanied by singing (Eens, 1997), and males tend to avoid nest boxes broadcasting complex male starling song (Mountjoy & Lemon, 1991).…”
Section: Introductionmentioning
confidence: 99%